2015
DOI: 10.1186/s13742-015-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Addressing health disparities in Hispanic breast cancer: accurate and inexpensive sequencing of BRCA1 and BRCA2

Abstract: BackgroundGermline mutations in the BRCA1 and BRCA2 genes account for 20–25 % of inherited breast cancers and about 10 % of all breast cancer cases. Detection of BRCA mutation carriers can lead to therapeutic interventions such as mastectomy, oophorectomy, hormonal prevention therapy, improved screening, and targeted therapies such as PARP-inhibition. We estimate that African Americans and Hispanics are 4–5 times less likely to receive BRCA screening, despite having similar mutation frequencies as non-Jewish C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…We identified facilitators and barriers to the use of BRCA genetic counseling among Latinas, none of whom reported that they had previously undergone this service, despite the fact that about 35% of the sample had undergone BRCA testing. These factors are important to consider given that there are significant disparities in the use of genetic services among this underserved group (Dean et al 2015;Gammon et al 2011;Levy et al 2011;Lynce et al 2016;Pagán et al 2009). Consistent with prior research, we found that the majority of participants demonstrated very low levels of awareness and knowledge about the benefits of genetic counseling, BRCA mutations, and increased risk associated with HBOC (Gammon et al 2011;Kinney et al 2010;Lynce et al 2016;Mai et al 2014;Sussner et al 2010Sussner et al , 2013Sussner et al , 2015Vadaparampil et al 2010a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified facilitators and barriers to the use of BRCA genetic counseling among Latinas, none of whom reported that they had previously undergone this service, despite the fact that about 35% of the sample had undergone BRCA testing. These factors are important to consider given that there are significant disparities in the use of genetic services among this underserved group (Dean et al 2015;Gammon et al 2011;Levy et al 2011;Lynce et al 2016;Pagán et al 2009). Consistent with prior research, we found that the majority of participants demonstrated very low levels of awareness and knowledge about the benefits of genetic counseling, BRCA mutations, and increased risk associated with HBOC (Gammon et al 2011;Kinney et al 2010;Lynce et al 2016;Mai et al 2014;Sussner et al 2010Sussner et al , 2013Sussner et al , 2015Vadaparampil et al 2010a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, despite the benefits of genetic counseling and testing for hereditary breast and ovarian cancer (HBOC) risk, significant disparities exist in the use of these services between women of non-Latina and Latina descent. While statistics are not available for genetic counseling alone, many studies indicate that awareness and use of genetic testing among Latinas is low (Dean et al 2015;Gammon et al 2011;Levy et al 2011;Lynce et al 2016;Mai et al 2014;Pagán et al 2009). In a recent study among at-risk Latina and non-Latina participants who had not previously undergone genetic counseling/testing, 57% of Latinas were unaware of the availability of BRCA testing, with Latina ethnicity the only notable factor associated with lack of awareness (Gammon et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Eight high risk variants in BRCA1 and BRCA2 were identified among African Americans and Puerto Ricans (Dean et al. ). Among the non‐malignant conditions identified in Puerto Ricans and African Americans were transthyretin amyloidosis ( TTR NM_000371.3:c.424G>A(p.Val142Ile)) that typically manifests after age 60 with renal amyloidosis and cardiomyopathy (Jacobson et al.…”
Section: Resultsmentioning
confidence: 99%
“…5 If used and interpreted appropriately, 23andMe's test could be a powerful tool for cancer prevention for this group of womennot just for one individual but for an entire family. More broadly, if developed, DTC tests for genetic variants associated with cancer risks that are common in other populations, such as African American and Hispanic women, who are 4 to 5 times less likely than women of Western European descent to undergo BRCA screening despite facing similar mutation rates, 6 could be game changers in democratizing access to such information.…”
Section: Significance Of the Fda's Decisionmentioning
confidence: 99%